The Influence of Using Teaching Aids on Student Learning Outcomes in the Learning Process in the Science Study Field - Megawati A; Muh Natsir; Aryandi Sudika; Wahyuni Wahyuni (International Journal on Advanced Science, Education, and Religion, 2024)
The aim of the research is to examine whether there is an influence of the use of teaching aids on the learning outcomes of students in the field of science study class IV at SDN Limbung Puteri, Bajeng District, Gowa Regency. This research aims to determine the influence of the use of teaching aids in the learning process in the field of science study class IV at SDN Limbung Puteri, Bajeng District, Gowa Regency. This type of research is pre-experimental research in the form of Pretest Posttest Design, namely an experiment which in its implementation only involves one class as an experimental class without a comparison class (control class) which aims to determine the effect of using teaching aids on student learning outcomes in the learning process in the field of study. Class IV Science at SDN Limbung Puteri, Bajeng District, Gowa Regency, 2016/2017 academic year. The experimental units in this research were 28 Class IV students. The research was carried out over 6 meetings. The success of the learning process is viewed from aspects, namely: achieving completeness of students' classical science learning outcomes and student activities in science learning. Learning is said to be successful if the above aspects are fulfilled. The data collection technique used is data on students' science learning outcomes which are collected using learning outcomes tests, data on student activities in science learning are collected using student learning activity observation sheets. The results of descriptive statistical analysis of student learning outcomes regarding positive teaching aids, understanding of material and concepts from science using teaching aids as media show better learning outcomes than before using teaching aids. The results of inferential statistical analysis using the t-test formula, it is known that the calculated t value obtained is 8.32 with a frequency of dk = 28 –1 = 27, at a significance level of 5% obtained t table = 0.381. So, t count > t table or the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that the use of teaching aids in science learning has an influence compared to before using teaching aids as learning media.